Prevalence of Osteoporosis and Osteopenia in Thai Female Patients at Rajavithi Hospital - Saengsuda, Sureerat (Journal of Health Science of Thailand, 2017)
The objective of this retrospectwe study was to determine the prevalence of osteoporosis in female patients who underwent bone mineral density measurement at Rajavithi hospital. Associated risk factors were also determined. The study included 750 women, age 50 years and over, and evaluated for bone mineral density using Dual energy X-ray absorptiometry at nuclear medicine section in Rajavithi hospital from June 2011 to June 2012. A diagnosis of osteoporosis was made according to WHO criteria. It was found that the prevalence of osteoporosis at either lumbar spine or femoral neck was 21.6 percent, which consisted of 9 percent with osteoporosis at lumbar spine only, 6.3 percent with osteoporosis at femoral neck only, and 6.3 percent with osteoporosis at both the lumbar spine and femoral neck. The prevalences of osteoporosis were 15.3 percent for lumbar spine and 12.6 percent for femoral neck. The prevalence of osteopenia at either lumbar spine or femoral neck was 59.4 percent, which consisted of 13.6 percent with osteopenia at lumbar spine only, 23.3 percent with osteopenia at the femoral neck only, and 22.5 percent with osteoporosis at both lumbar for femoral neck. The prevalences of osteopenia were 36.1 percent for lumbar spine and 45.8 percent for femoral neck. The prevalence of osteoporosis increased with age after 50 years of age. Osteoporosis group had significantly higher mean age, lower mean height, lower mean bodyweight and lower body mass index than osteopenia and normal groups (p-value <0.001). The prevalences of osteoporosis are in accordant with Thai and Asian reports but higher than those of the United State population. Older age, lower weight, decreased height and low body mass index (BMI) are significant risk factors for osteoporosis.